Buddha in Beton Eine buddhologische Kritik der neuen Wege des japanischen Tempelbaus - Gerlach, Jonas (Modern Academic Publishing, 2017)
emple. And only because temple architecture - as well as paintings, statues, gardens etc. - shows the presence of the Buddha in this way does it become a religious place where the Buddha is actually present. The final discussion of this study puts these Buddhist teachings in a dialogue with modern aesthetic architectural concepts argued by temple architects. The contrasting points of view make it clear that the explicitly Buddhist idea of Buddhist temple architecture can not be grasped by aesthetics, because its purpose is to show the invisible presence of the Buddha and not to be a sensual (i.e. aesthetic) experience of the visible object itself in the first place. However, aesthetic concepts of art have become common in Japan since the late 19th century. They are the foundation of the described new ways in which temples were built and designed since then. One indication for the impact of aesthetics are Japanese words like shimboru シンボル/shōchō 象徴 (symbol) or fun'iki 雰囲気 (atmosphere) which are used by architects to describe their temple architecture and matters of design. These words were formed around the turn of the century to express European concepts of art and aesthetics, since before that these words and ideas simply did not exist in Japan. And it is only since then, that temples were perceived as aesthetic symbols with various meanings that can be defined by an architect, and that they have a certain atmosphere which should be designed for making visitors feeling comfortable. Now it is the architect himself who gives meaning to its work and who is responsible for a nice spatial experience. But none of these architects is talking about himself becoming Buddha by building a temple. So not only the architectural appearance and construction of Buddhist temples have changed enormously throughout the last 150 years, but also the task of building itself. There has always been change in appearance and construction throughout the history of Buddhism and in the different Buddhist cultures, but the redefinition of the temple as an architectural piece of art is a very recent development in Japan and the actual new idea causing these dramatic architectural changes. "